2015
DOI: 10.1136/jnnp-2015-312283
|View full text |Cite
|
Sign up to set email alerts
|

Parkinson disease male-to-female ratios increase with age: French nationwide study and meta-analysis

Abstract: BackgroundParkinson’s disease (PD) is 1.5 times more frequent in men than women. Whether age modifies this ratio is unclear. We examined whether male-to-female (M–F) ratios change with age through a French nationwide prevalence/incidence study (2010) and a meta-analysis of incidence studies.MethodsWe used French national drug claims databases to identify PD cases using a validated algorithm. We computed M–F prevalence/incidence ratios overall and by age using Poisson regression. Ratios were regressed on age to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
111
2
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 199 publications
(127 citation statements)
references
References 36 publications
(38 reference statements)
11
111
2
3
Order By: Relevance
“…However, this would considerably complicate the estimation process and would require additional input data that are not available at the present time. Another limitation is that we probably failed to identify some patients (eg, untreated or undiagnosed, in institutions with in‐house pharmacies), but we were able to correct our frequency estimates for the sensitivity and specificity of the method used to identify PD patients, and we previously showed that our frequency estimates are consistent with those from other studies . In addition, we took into account the underestimation in the oldest persons by correcting estimates for underdiagnosis after age 80.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…However, this would considerably complicate the estimation process and would require additional input data that are not available at the present time. Another limitation is that we probably failed to identify some patients (eg, untreated or undiagnosed, in institutions with in‐house pharmacies), but we were able to correct our frequency estimates for the sensitivity and specificity of the method used to identify PD patients, and we previously showed that our frequency estimates are consistent with those from other studies . In addition, we took into account the underestimation in the oldest persons by correcting estimates for underdiagnosis after age 80.…”
Section: Discussionmentioning
confidence: 89%
“…First, PD patients were identified in the French National Health Insurance database (SNIIRAM) using a prediction model based on drug claims that allow one to estimate the probability that people who used antiparkinsonian drugs in a given year are being treated for PD . We have previously shown that this approach identifies treated patients with 92.5% sensitivity and 86.4% specificity and yields age‐ and gender‐specific incidences consistent with 22 previously published studies . We applied this prediction model for years 2009 to 2012.…”
Section: Methodsmentioning
confidence: 92%
See 2 more Smart Citations
“…Prevalence and incidence male/female (M/F) ratios increase by 0.05 and 0.14, respectively, per 10 years of age. Incidence is similar in men and women under 50 years (M/F ratio < 1.2), and over 1.6 times higher in men than women above 80 years [8]. Furthermore, PD coexists with dementia in over 25% of the cases and with depression in over 30% of the cases in some countries [7].…”
Section: Introductionmentioning
confidence: 99%